Racial discrimination and health: exploring the possible protective effects of ethnic density - Stafford, Mai (Ethnicity and Integration, 2010)
The work described in this chapter aims to widen the focus of research on ethnicity and health to highlight how the residential context can shape the everyday experiences and health of ethnic minority groups. Ethnic inequalities in health are well documented, with both a poorer economic position and exposure to racism leading to poorer health for several of the UK’s ethnic minority groups. However, an emerging literature suggests that ethnic density may mitigate some of these effects. Possible protective pathways that may link greater ethnic density to better ethnic minority health are explored.